Dampak Social Proof dan Retensi Pelanggan di UMKM Café di Kota Bandung: Tinjauan Literatur - Laetitia, Amara (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2025)
This study explores the crucial role of social proof and customer retention in modern marketing strategies, particularly for UMKM cafés in Bandung. Social proof, introduced by Robert Cialdini, describes the tendency of individuals to mimic the actions of others in uncertain situations, especially through online reviews and testimonials. In the digital era, social proof significantly impacts consumer purchasing behavior. Conversely, customer retention reflects a business's ability to maintain its clientele, directly correlating with customer satisfaction and repeat purchases. High retention rates not only reduce marketing costs but also enhance profitability. The paper proposes integrating social proof strategies, such as positive online reviews and local influencer endorsements, along with loyalty programs and personalized services to boost customer loyalty. By effectively managing customer perceptions through social media and online reviews, UMKM cafés in Bandung can build a strong reputation and compete in a saturated market, ensuring sustained business growth and customer satisfaction.